The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.14412/1995-4484-2018-500-505
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Coxitis in Patients With Ankylosing Spondylitis

Abstract: The review analyzes the foreign and Russian literature published in the past 30 years and devoted to the diagnosis and treatment of coxitis in ankylosing spondylitis (AS). The results of previous works have revealed the high rate of hip joint injury (HJI) in AS, but it is still unclear which diagnostic technique is the most sensitive for the early detection of coxitis. The latter has been shown to serve as one of the predictors of early disability in patients. The most studied treatment for coxitis is now HJI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
3
0
3
Order By: Relevance
“…As hip joint involvement in AS has a serious negative impact on the course of the disease, findings concerning the effect of AS therapy on the progression of coxitis are clinically valuable. 2,4 Here we report the results of the long-term real-world-evidence S3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As hip joint involvement in AS has a serious negative impact on the course of the disease, findings concerning the effect of AS therapy on the progression of coxitis are clinically valuable. 2,4 Here we report the results of the long-term real-world-evidence S3.…”
Section: Discussionmentioning
confidence: 99%
“…2 It has been reported that the hip joint is involved in 24%-54% of AS cases. [3][4][5] Hip joint inflammation (coxitis) dramatically worsens patient mobility and quality of life and is associated with worse Bath Ankylosing Spondylitis Functional Index (BASFI) score and disease outcomes. 2 Joint inflammation in AS leads to different types of structural damage: inappropriate osteogenesis in the spine and sacroiliac joints and destructive erosive processes in the hip joints.…”
Section: Introductionmentioning
confidence: 99%
“…При включении в исследование Ск-прК в группе наблюдения (n=62) составила в среднем 0,45 (условно было принято, что в начале заболевания у пациентов не было признаков поражения ТБС: ссрК=0). В первый год Ск-прК составила 0,54, во второй -0, 1…”
Section: материал и методыunclassified
“…с отсутствием стойких клинических проявлений нередко приводит к его позднему выявлению, когда имеются необратимые рентгенологические изменения, в большинстве случаев требующие эндопротезирования ТБС [1]. По данным исследований, проведенных в Российской Федерации и посвященных проблеме коксита, признаки поражения ТБС выявляются примерно у каждого второго пациента с анкилозирующим спондилитом (АС) [2].…”
unclassified
“…Компонентами коксита могут быть синовит, энтезит и воспалительное поражение костного мозга костей сустава [3]. Клинические характеристики коксита включают типичную паховую (ингвинальную) боль с ограничением или болезненностью движений в ТБС.…”
unclassified